Zinc supplementation is associated with a reduction in serum markers of inflammation and oxidative stress in adults: A systematic review and meta-analysis of randomized controlled trials. (February 2021) - Hosseini, Razieh; Ferns, Gordon A.; Sahebkar, Amirhossein; Mirshekar, Mohammad Ali; Jalali, Mohammad
Graphical abstract: Highlights: Zinc (Zn) is a trace metal that is considered to have an impact on chronic inflammation. Zn supplementation improved serum C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α) and malondialdehyde (MDA). Through meta-regression, treatment duration was found as the source of inter-study heterogeneity. Abstract: Background: Zinc (Zn) is a trace metal that is considered to have an impact on chronic inflammation. However, findings of clinical trials have been inconsistent. The present systematic review and meta -analysis aimed to provide a more robust examination of the evidence on the effectiveness of Zn supplements on markers of inflammation and oxidative stress. Methods: A systematic search in PubMed, Scopus, Web of Science and Cochrane Library was undertaken to identify relevant randomized controlled trials (RCTs) assessing the impact of Zn on inflammation and oxidative stress until 17 August 2020. We applied a random-effects method to obtain effect sizes (ES) and 95% confidence intervals (CIs). Meta-regression was used to detect the potential source of between-study heterogeneity. Results: Twenty-one eligible RCTs comprising 1321 participants were included in the meta -analysis. In comparison with the control groups, serum C-reactive protein (CRP) (ES = −0.92 mg/L, 95% CI = [−1.36, −0.48], P  < 0.001, I 2  = 90.2%), tumor necrosis factor-alpha (TNF-α) (ES = −0.49 pg/mL, 95% CI = [−084, −0.14], P  = 0.006, I 2  = 34.6%) and malondialdehyde (MDA) (ES = −0.42, 95% CI = [−083, −0.01], P  = 0.04, I 2  = 76.1%) were significantly reduced in the groups receiving Zn. Serum interleukin 6 (ES = −1.02 pg/mL, 95% CI = [−2.06, 0.02], P  = 0.05, I 2  = 92.3%) was marginally reduced following Zn supplementation. Moreover, treatment duration was found as the source of inter-study heterogeneity. Conclusion: This meta-analysis suggests that Zn supplements reduce serum concentrations of markers of inflammation and oxidation: CRP, TNF-α and MDA.